Outbreaks of an Emerging Viral Disease Covary With Differences in the Composition of the Skin Microbiome of a Wild United Kingdom Amphibian - Campbell, Lewis J.; Garner, Trenton W. J.; Hopkins, Kevin; Griffiths, Amber G. F.; Harrison, Xavier A. (Frontiers in Microbiology, 2019)
There is growing appreciation of the important role of commensal microbes in ensuring the normal function and health of their hosts, including determining how hosts respond to pathogens. A range of infectious diseases are threatening amphibians worldwide, and evidence is accumulating that the host-associated bacteria that comprise the microbiome may be key in mediating interactions between amphibian hosts and infectious pathogens. We used 16S rRNA amplicon sequencing to quantify the skin microbial community structure of over 200 individual wild adult European common frogs (Rana temporaria), from ten populations with contrasting history of the lethal disease ranavirosis, caused by emerging viral pathogens belonging to the genus Ranavirus. All populations had similar species richness irrespective of disease history, but populations that have experienced historical outbreaks of ranavirosis have a distinct skin microbiome structure (beta diversity) when compared to sites where no outbreaks of the disease have occurred. At the individual level, neither age, body length, nor sex of the frog could predict the structure of the skin microbiota. Our data potentially support the hypothesis that variation among individuals in skin microbiome structure drive differences in susceptibility to infection and lethal outbreaks of disease. More generally, our results suggest that population-level processes are more important for driving differences in microbiome structure than variation among individuals within populations in key life history traits such as age and body size.